2012
DOI: 10.1371/journal.pone.0029617
|View full text |Cite
|
Sign up to set email alerts
|

Using Knowledge Fusion to Analyze Avian Influenza H5N1 in East and Southeast Asia

Abstract: Highly pathogenic avian influenza (HPAI) H5N1, a disease associated with high rates of mortality in infected human populations, poses a serious threat to public health in many parts of the world. This article reports findings from a study aimed at improving our understanding of the spatial pattern of the highly pathogenic avian influenza, H5N1, risk in East-Southeast Asia where the disease is both persistent and devastating. Though many disciplines have made important contributions to our understanding of H5N1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
4
6
0
Order By: Relevance
“…In this case, areas with a higher poultry density might not necessary have a higher risk. Hence, in line with previous findings in China [17], [18], we also found that an increased poultry density did not lead to an increased risk of HPAI H5N1 outbreak. The intensive commercial poultry production systems in Europe may have a relatively high level of bio-security, in contrast to some regions where poultry are free ranging during daylight hours, such as the free-grazing poultry areas in the Danube River delta [5].…”
Section: Discussionsupporting
confidence: 92%
“…In this case, areas with a higher poultry density might not necessary have a higher risk. Hence, in line with previous findings in China [17], [18], we also found that an increased poultry density did not lead to an increased risk of HPAI H5N1 outbreak. The intensive commercial poultry production systems in Europe may have a relatively high level of bio-security, in contrast to some regions where poultry are free ranging during daylight hours, such as the free-grazing poultry areas in the Danube River delta [5].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies indicated that per capita GDP and TB incidence at the provincial level had a negative relationship. Similar results were observed for other infectious diseases such as SARS and H5N1 [4,57]. Therefore, improving the local economy is bene cial to the control of TB in the origin.…”
Section: Discussionsupporting
confidence: 78%
“…Altitude (or elevation) has been applied as a significant predictor in a number of studies of infectious diseases, including TB (Saito et al, 2006) and avian influenza (Gilbert et al, 2008;Ge et al, 2012). In particular, altitude has a protective effect against TB in Peru in which lower disease prevalence and increased household clustering of TB was found in high altitude villages compared to those at sea level (Saito et al, 2006).…”
Section: Tuberculosismentioning
confidence: 99%
“…All data were converted into 1 Â 1 square kilometer lattice. This spatial resolution was chosen because it is a broadly accepted spatial unit for ecological studies (Ge et al, 2012;Qiu et al, 2014). Moreover, research have shown that an individual's activity space varies between 800 and 1000 meters and that a finer spatial resolution may cause structural clutter that affects decision-making (Lai et al, 2015).…”
Section: Data Sourcesmentioning
confidence: 99%